2019
DOI: 10.1136/esmoopen-2019-000491
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of BRAF/MEK inhibitor combinations: adverse event evaluation and management

Abstract: The inhibition of the mitogen-activated protein kinases signalling pathway through combined use of BRAF and MEK inhibitors (BRAFi+MEKi) represents an established therapeutic option in patients with BRAF-mutated, advanced melanoma. These efficient therapies are well tolerated with mostly moderate and reversible side effects and a discontinuation rate due to adverse events of 11.5%–15.7%. Median duration of therapy ranges between 8.8 and 11.7 months. Based on data from confirmatory trials, safety profiles of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 90 publications
2
163
0
9
Order By: Relevance
“…They also inhibit other growth factors and kinases including c-kit protein, platelet-derived growth factor receptor (PDGFR), and FMS-like tyrosine kinase-3 [ 107 , 108 ]. The B-rapid accelerating fibrosarcoma (BRAF) (dabrafenib, vemurafenib, encorafenib) and mitogen extracellular signal-regulated kinase (MEK) inhibitors (trametinib, cobimetinib, binimetinib) are serine-threonine kinase inhibitors that are active against V600 mutations in melanoma and colorectal carcinomas [ 39 ]. Hypertension of all grades remains a significant treatment adverse effect with these drugs, with evidence of a class effect.…”
Section: Hypertensive Cardiotoxicities Of Cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also inhibit other growth factors and kinases including c-kit protein, platelet-derived growth factor receptor (PDGFR), and FMS-like tyrosine kinase-3 [ 107 , 108 ]. The B-rapid accelerating fibrosarcoma (BRAF) (dabrafenib, vemurafenib, encorafenib) and mitogen extracellular signal-regulated kinase (MEK) inhibitors (trametinib, cobimetinib, binimetinib) are serine-threonine kinase inhibitors that are active against V600 mutations in melanoma and colorectal carcinomas [ 39 ]. Hypertension of all grades remains a significant treatment adverse effect with these drugs, with evidence of a class effect.…”
Section: Hypertensive Cardiotoxicities Of Cancer Therapiesmentioning
confidence: 99%
“…Ibrutinib and lenvatinib were associated with the highest rate of all grade hypertension 49–68% and high grade CTCAE 3 or 4 hypertension in 16–42%, respectively. The BRAF and MEK inhibitors, typically used in combination therapy for melanoma with V600 mutations, evoked a hypertensive response of any grade in 20.6% and CTCAE grade 3 or 4 in 10.1% [ 39 ].…”
Section: Hypertensive Cardiotoxicities Of Cancer Therapiesmentioning
confidence: 99%
“…In fact, in most of the cell lines with BRAF mutations, IC 50 of vemurafenib is nearly one order of magnitude greater than that observed for of dabrafenib (<1,000 nmol/L vs. <100 nmol/L, respectively) (28). In addition, according to the biopharmaceutics classification system, vemurafenib is classified with low solubility-low permeability properties, differing from the low solubility-high permeability classification of dabrafenib (29)(30)(31). On these bases, it is reasonable to expect that the anti-proliferative effects of these two drugs may reverberate differentially on the reproductive function and in particular on spermatogenesis which is highly sensitive to environmental noxae (32).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of immunotherapy drugs for people who have less advanced melanoma was evaluated by Heinzerling et al They showed the efficiency of BRAF and MEK inhibitors (BRAFi + MEKi), combined, as an established therapeutic option in patients with BRAF-mutated advanced melanoma. In particular, the dabrafenib + trametinib (D + T) combination has been demonstrated to prolong overall survival in the adjuvant setting [67].…”
Section: Pairing Therapiesmentioning
confidence: 99%